Contribution of vitamin D3 and thiols status to the outcome of COVID-19 disease in Italian pediatric and adult patients - Annamaria D’Alessandro; Domenico Ciavardelli; Anna Pastore; Santina Lupisella; Rosa Carmela Cristofaro; Giovina Di Felice; Roberta Salierno; Marco Infante; Alberto De Stefano; Andrea Onetti Muda; Maria Morello; Ottavia Porzio (Scientific Reports, 2023)
Abstract The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV-2), was declared a global pandemic by the World Health Organization (WHO) on March 2020, causing unprecedented disease with million deaths across the globe, mostly adults. Indeed, children accounted for only a few percent of cases. Italy was the first Western country struck by the COVID-19 epidemic. Increasing age, which is one of the principal risk factors for COVID-19 mortality, is associated with declined glutathione (GSH) levels. Over the last decade, several studies demonstrated that both vitamin D (VD) and GSH have immunomodulatory properties. To verify the association between VD, GSH and the outcome of COVID-19 disease, we conducted a multicenter retrospective study in 35 children and 128 adult patients with COVID-19. Our study demonstrated a hypovitaminosis D in COVID-19 patients, suggesting a possible role of low VD status in increasing the risk of COVID-19 infection and subsequent hospitalization. In addition, we find a thiol disturbance with a GSH depletion associated to the disease severity. In children, who fortunately survived, both VD and GSH levels at admission were higher than in adults, suggesting that lower VD and thiols levels upon admission may be a modifiable risk factor for adverse outcomes and mortality in hospitalized patients with COVID-19.